A New Synthesis Strategy for Rhodanine and Its Derivatives - Pan, Zhenliang; An, Wankai; Wu, Lulu; Fan, Liangxin; Yang, Guoyu; Xu, Cuilian (Synlett, 2021)
Rhodanine and its derivatives have been known as privileged structures in pharmacological research because of their wide spectrum of biological activities, but the synthesis method of rhodanine skeleton is limited. In this paper, not only rhodanine skeleton, but also N-aryl rhodanines can be directly prepared via the reaction of thioureas and thioglycolic acid in one step catalyzed by protic acid, which provides a new approach of the synthesis of rhodanine and its derivatives. The developed strategy is straightforward, efficient, atom economical, and convenient in good yields.
Keywords: rhodanine; thiourea; thioglycolic acid; thiazolidone; heterocycle